Slaughterhouse Waste Treatment Equipment to Produce Plant Fertilizer and Fish Feed - Rindi Kusumawardani; Putu Dana Karningsih; Nani Kurniati; Moses Laksono Singgih; Hari Supriyanto; Sutikno Sutikno; Dwa Desa Warnana; Irene Malilung Sitanggang (IPTEK Journal of Proceedings Series, 2023)
Chicken slaughter process waste is divided into two types, solid waste and liquid waste. Almost all of the waste generated by the chicken slaughter process can be reused. Lately, Vocational High School in Pasuruan, East Java, has Livestock Agribusiness unit that made a waste treatment program to deal with the problem of waste from the surrounding chicken slaughter process. However, some chicken slaughter process waste cannot be reprocessed and is directly dumped into the sewer due to limited technology. The type of waste that cannot reprocess is blood and chicken feather waste. This research aims to process the waste into high-quality fish food by applying the principle of automation and integrating machines with existing chicken cutting machines. The application of this appropriate technology begins with observing the existing conditions and the process of designing, manufacturing, and testing equipment carried out at Vocational High School in Pasuruan. The research resulted in designing and manufacturing machines that support waste treatment of blood and chicken feathers from Livestock Agribusiness. The machine design consists of three main components: a blood and chicken feather grinder, a vertical mixer, and a fish feed press machine. The expectations of this machine design will support productivity and concern for waste management, which can also build environmentally friendly standards in the Livestock Agribusiness unit of Vocational School in Pasuruan.